The contribution of a whey protein film incorporated with green tea extract to minimize the lipid oxidation of salmon (Salmo salar L.) - Castro, Frederico V R (2020)
Active packaging is becoming progressively more significant as a response to the dynamic changes in current consumer demand and market tendencies. Active packaging is projected to interact directly with the packaged food or with the headspace within the package with the aim of maintaining or extending product quality and shelf-life. Aiming for sustainability, the potential application as biodegradable films of whey protein concentrate (WPC) was evaluated. Aromatic plant's extracts present high antioxidant properties, representing an alternative for synthetic food additives. The main objective of this study was to verify the effectiveness of an edible WPC film incorporated with a plant-based extract on retarding the lipid oxidation of fresh salmon. Green tea extract (GTE) was chosen to be incorporated into the active film. Fresh salmon was packaged with the control film (WPC) and with active film (WPC-GTE). The oxidation level of non-packaged samples and packaged samples were tested for different storage times. Four methods were applied to evaluate lipid oxidation state of fresh salmon: peroxide value, p-anisidine value, thiobarbituric acid reactive substances (TBARS) assay, and monitoring of hexanal. The results obtained in this study indicate that the whey protein active film was successfully produced, and it was effective in delaying lipid oxidation of fresh salmon samples until the 14th day of storage.